Offsetting Uncertainty: Reassurance with Two‐Sided Incomplete Information. Issue 1 (9th September 2019) - Haynes, Kyle; K. Yoder, Brandon
Abstract: Conventional models of bargaining and reassurance under incomplete information assume that actors' behavioral signals are objectively cooperative or noncooperative. Even if actors are uncertain of each other's preferences, they know what types of actions the other will view as cooperative. Yet on many real‐world issues, cooperation is subjective, and what constitutes a cooperative action is conditional on the receiver's preferences. We present a formal model showing that in these cases, two‐sided incomplete information actually incentivizes honest behavior and facilitates credible signaling. Because uncertain senders do not know whether a particular action will be interpreted as cooperative, they have little incentive to misrepresent, and instead honestly pursue their true goals. Thus, where cooperation is subjective, mutual uncertainty is "offsetting, " such that credible signals allow actors to quickly and accurately update their beliefs. We illustrate this logic through a case study of the Sino–Soviet split, and highlight the model's implications for contemporary U.S.–China relations.